Deep sea benthic foraminifera of the Panama basin: Ecology and their possible relation with deep sea currents (2013)
Deep sea benthic foraminifera of the Panama basin: ecology and their possible relation with deep sea currents. The relationship between recent benthic foraminifera and bottom currents in the Panama basin (Colombian Pacific) is examined, and the main ecological variables which control the distribution of benthic foraminifera are discussed. The benthic foraminiferal study of 24 core top samples and the integration with previous reports, support the view that in upwelling areas or under high terrigenous influx, the assemblages are dominated by infaunal forms such as Uvigerina, Bolivina, Globobulimina, and Chilostomella, beside common forms such as Uvigerina peregrina Cushman and Epistominella spp., which are indicative of high productivity. In contrast, epifaunal forms such as Cibicidoides, Laticarinina, and Hoeglundina are more common on the flanks of the Cocos and CarnegieRidges indicating a lower surface productivity and a larger content of dissolved oxygen on the sea foor. Infaunal foraminifera are dominated by Siphouvigerina proboscidea (Schwager). In addition, several proxy taxa of the intensity of deep sea currents were detected in the analyzed assemblages. From these taxa, Cibicides wuellerstorf (Schwager) has the best proxy potential for the reconstruction of intense bottom currents in sediments from the Cocos and Carnegie Ridges for the Holocene.